The Extent to Which Menstruation-Related Issues Are Included in Graduate-Level Public Health Curricula - Sommer, Marni; Lee, Christina; Liu, Danting; Gruer, Caitlin (Frontiers in Public Health, 2020)
Objectives: Menstruation is increasingly recognized as an issue in domestic and global public health. Public health graduates of U.S. schools of public health must have adequate competencies to address menstruation and its implications for health and wellbeing in their future endeavors in research, practice and policy. This study sought to understand the extent to which U.S. schools currently integrate menstruation-related content (menstrual health, menstrual hygiene, etc.) and related competencies into their curricula. Methods: We reviewed the course directories of the top twenty US schools of public health as ranked in 2018. Courses were selected based on inclusion of menstruation and adolescent health-related search terms. Syllabi were subsequently obtained and analyzed for inclusion of specific menstruation-related terms. Syllabi including these terms were further analyzed to determine the level of inclusion of menstruation-related topics in relation to public health competencies, and the area of specialization. Results: Of an estimated 5,000 courses assessed, twenty-eight included menstruation-related topics. Most frequently, this inclusion was minimal (e.g. a single reading or assignment), and was limited in scope. Content was typically found within global health, environmental health, and maternal and child health. Conclusions: Given growing attention to menstruation domestically and globally, and the limited current inclusion of this issue in US schools of public health curricula, graduates may not be receiving adequate training on a critically important topic of relevance within population health. Schools should consider reviewing their curricula to assess whether there are opportunities to integrate menstruation-related content in relation to the relevant public health competencies.